Co‐Self‐Assembled Monolayers Modified NiOx for Stable Inverted Perovskite Solar Cells - Cao, Qi; Wang, Tianyue; Pu, Xingyu; He, Xilai; Xiao, Mingchao; Chen, Hui; Zhuang, Lvchao; Wei, Qi; Loi, Hok‐Leung; Guo, Peng; Kang, Bochun; Feng, Guangpeng; et al. (Advanced materials (Weinheim), 2024)
[4‐(3,6‐dimethyl‐9H‐carbazol‐9yl)butyl]phosphonic acid (Me‐4PACz) self‐assembled molecules (SAM) are an effective method to solve the problem of the buried interface of NiOx in inverted perovskite solar cells (PSCs). However, the Me‐4PACz end group (carbazole core) cannot forcefully passivate defects at the bottom of the perovskite film. Here, a Co‐SAM strategy is employed to modify the buried interface of PSCs. Me‐4PACz is doped with phosphorylcholine chloride (PC) to form a Co‐SAM to improve the monolayer coverage and reduce leakage current. The phosphate group and chloride ions (Cl−) in PC can inhibit NiOx surface defects. Meantime, the quaternary ammonium ions and Cl− in PC can fill organic cations and halogen vacancies in the perovskite film to enable defects passivation. Moreover, Co‐SAM can promote the growth of perovskite crystals, collaboratively solve the problem of buried defects, suppress nonradiative recombination, accelerate carrier transmission, and relieve the residual stress of the perovskite film. Consequently, the Co‐SAM modified devices show power conversion efficiencies as high as 25.09% as well as excellent device stability with 93% initial efficiency after 1000 h of operation under one‐sun illumination. This work demonstrates the novel approach for enhancing the performance and stability of PSCs by modifying Co‐SAM on NiOx. Phosphorylcholine chloride and Me‐4PACz are used to form Co‐SAM on the NiOx surface to optimize the buried interface in PSCs. Co‐SAM can promote the growth of perovskite crystals, passivate buried defects, optimize the energy band alignment, and relieve the residual stress of the perovskite film, leading to power conversion efficiencies as high as 25.09% and excellent device stability.